2017
DOI: 10.14260/jemds/2017/204
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variations of Sphenoidal Inter-Sinus Septa in Terms of Number and Attachments - A Ct Finding

Abstract: BACKGROUNDSphenoid sinus is an important structure located in the body of the sphenoid bone. It is separated from critical surrounding structures like optic nerve and chiasm, cavernous sinus, pituitary gland and internal carotid artery by a thin bony lamella. Because of its location and close relation to these important anatomical structures, diagnosis and treatment of sphenoid sinus pathologies are very challenging. In the era of endoscopic approach to the sphenoid sinus and skull base, the detailed knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…In our study 67.85% of scans were having single septum (47.87% complete and 20% incomplete) and multiple septum were present in rest of the scans (15.71% double septum and 16.42% triple septum). In previous studies, single septum was recorded from 61% to as high as 95% and multiple septa were cited between 7% to 95% scans [7,8,9,10] . In this study multiple septa are present in 45 cases (32.14%).…”
Section: Discussionmentioning
confidence: 99%
“…In our study 67.85% of scans were having single septum (47.87% complete and 20% incomplete) and multiple septum were present in rest of the scans (15.71% double septum and 16.42% triple septum). In previous studies, single septum was recorded from 61% to as high as 95% and multiple septa were cited between 7% to 95% scans [7,8,9,10] . In this study multiple septa are present in 45 cases (32.14%).…”
Section: Discussionmentioning
confidence: 99%
“…The main septum it is located in the midline but usually deviated to one side, making an asymmetrical appearance of the sella turcica floor (20). We could also notice the presence of an incomplete septum in three cases (1, 3 and 4), this feature has a low prevalence published on literature (6,15). This characteristic could be explain in the fact of the Peruvian population is predominantly half blood, and there is not a specific patron.…”
Section: Discussionmentioning
confidence: 58%
“…Of particular note, among limited studies reported from India, Kirtane et al have evaluated the use of vidian neurectomy for crocodile tears, a sequelae lesion of the facial nerve. 24 Bhanu Pratap Singh et al, 25 Sushil Kumar Kashyap et al 26 and Prabu SS 27 have noted protruded and dehiscent vidian canal while studying variations in sphenoid sinus. They have not evaluated the degree of pterygoid process pneumatization.…”
Section: Discussionmentioning
confidence: 99%